Fracture characterization of roller compacted concrete mixtures with blast furnace slag and industrial sand - Albuquerque, Maria C.F.; Balbo, José T.; Sansone, Eduardo C.; Pinto, Paulo C. (My University, 2011)
The global energy crisis and growing environmental concerns have prompted manufacturers in general to intensify their efforts to reuse the by-products and wastes they generate. In metallurgy, steel production generates dross in the form of slag. In the present study, roller-compacted concrete (RCC) mixtures were prepared and the sand fraction was composed with industrial sand and granulated blast furnace slag. The influence of these different fine aggregates was analyzed based on the compaction parameters (moisture and dry unit weight), indirect tensile strength, flexural strength, and modulus of elasticity. Toughness and fracture tests were carried out and R-curve was determined for the mixtures. It was found that the RCC mixtures containing slag required larger amounts of water for compaction, presented drops in tensile strength and modulus of elasticity as well as increased the mean values of propagation energy in little amount. Both the reference RCC and the slag RCC presented a consistently upward R-curve and, in absolute values, showed a better R-curve and KR performance than conventional and high-strength concretes previously studied in the literature. This is very important for paving purposes since a material with such a behavior shows greater resistance to catastrophic crack propagation, thus extending the service life of pavement layers. © Chinese Society of Pavement Engineering.
Keywords: Fracture mechanics; Granulated blast furnace slag; Roller-compacted concrete; Tensile strength; Toughness